Mesopotamia [Assyrians, Sumerians, Babylonians] - Ascalone, Enrico (Dictionaries of Civilizations, 2007)
"This beautifully illustrated guide to the ancient civilization of Mesopotamia, the region between the Tigris and Euphrates rivers, is the perfect companion for travelers and armchair travelers alike. It provides a concise survey of three ancient cultures that have often been misunderstood, both because of Biblical and neoclassical traditions, and because of twentieth- and twenty-first-century events. Lavishly illustrated in full color on every page, the book is arranged topically to cover the broad areas of life, such as people, politics, religion, the world of the dead, and important places and monuments. The text emphasizes the archaeological and literary evidence pertaining to Mesopotamia during the period before the arrival of Alexander the Great, beginning with the written sources, including the list of Sumerian kings and the epic of Gilgamesh, and continuing with the major personages, such as the Akkadian monarchy from Sargon through Nabonedo. The book also brings together the principal Mesopotamian works of art that have been dispersed in museums worldwide - notably the materials from the Baghdad Museum that were damaged or lost in the present war. Packed with information, images, maps, diagrams, and reconstructions, Mesopotamia is the perfect companion to an important ancient civilization." -- Publisher's description.